2011
DOI: 10.1890/09-2123.1
|View full text |Cite
|
Sign up to set email alerts
|

Body condition and pregnancy in northern Yellowstone elk: Evidence for predation risk effects?

Abstract: Abstract. S. Creel et al. reported a negative correlation between fecal progesterone concentrations and elk : wolf ratios in greater Yellowstone elk (Cervus elaphus) herds and interpreted this correlation as evidence that pregnancy rates of elk decreased substantially in the presence of wolves (Canis lupus). Apparently, the hypothesized mechanism is that decreased forage intake reduces body condition and either results in elk failing to conceive during the autumn rut or elk losing the fetus during winter. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 33 publications
6
56
0
Order By: Relevance
“…We concluded that ''although correlative, these results suggest that wolf predation has indirect effects on elk dynamics, driven by costs of behavioral defenses that alter reproductive physiology and demography.' ' White et al (2011) recently questioned our conclusions, using data from one herd in the Northern Range of Yellowstone National Park. First, they failed to detect changes in the mean pregnancy rate in a comparison of data from 1962-1968 (wolves absent) and [2000][2001][2002][2003][2004][2005][2006] (after wolf reintroduction).…”
Section: Behavioral and Ecological Responses Of Elkmentioning
confidence: 79%
See 4 more Smart Citations
“…We concluded that ''although correlative, these results suggest that wolf predation has indirect effects on elk dynamics, driven by costs of behavioral defenses that alter reproductive physiology and demography.' ' White et al (2011) recently questioned our conclusions, using data from one herd in the Northern Range of Yellowstone National Park. First, they failed to detect changes in the mean pregnancy rate in a comparison of data from 1962-1968 (wolves absent) and [2000][2001][2002][2003][2004][2005][2006] (after wolf reintroduction).…”
Section: Behavioral and Ecological Responses Of Elkmentioning
confidence: 79%
“…'S CRITIQUE The results just discussed provide consistent support for the hypothesis that the pregnancy rate of elk has declined in sites with high wolf-elk ratios. Still, it remains to be explained why this pattern was not apparent in the analysis of White et al (2011). While differences among populations in the strength of risk effects are expected, several aspects of their methods would be expected to obscure any effect of predation risk on pregnancy rates.…”
Section: Methodological and Statistical Problemsmentioning
confidence: 99%
See 3 more Smart Citations